2019
DOI: 10.7150/ijms.27610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of BCL2, C-MYC, and BCL6 Genetic Abnormalities, Epstein-Barr Virus Infection, CD5 Protein Expression, Germinal Center B Cell/Non-Germinal Center B-Cell Subtypes, Co-expression of MYC/BCL2 Proteins and Co-expression of MYC/BCL2/BCL6 Proteins in Diffuse Large B-Cell Lymphoma: A Clinical and Pathological Correlation Study of 120 Patients

Abstract: Background: Clinical significance of germinal center B-cell (GCB) and non-GCB sub-categorization, expression of MYC, BCL2, BCL6, CD5 proteins and Epstein Barr virus encoded RNA (EBER) positivity in diffuse large B-cell lymphoma (DLBCL) remain controversial. Could these biomarkers accurately identify high risk DLBCL patients? Are MYC, BCL2 and BCL6 proteins expression feasible as baseline testing to predict c-Myc , BCL2 or BCL6 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 45 publications
2
26
3
2
Order By: Relevance
“…IHC interpretation was performed by hematopathologists or other pathologists nearly three-quarters of the time (30/41, 73.2%). In brief, the study design was prospective in one study [59], retrospective in 22 [3,32,33,36,[38][39][40]42,[44][45][46][47][49][50][51]54,60,61,63,66,67,69], secondary analysis of primary clinical trials in six [37,41,48,53,57,58], and not-explained in 12 [19][20][21]34,35,43,52,55,56,62,65,68]. The number of patients per study ranged from 20 to 688, with median ages of 46-70 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…IHC interpretation was performed by hematopathologists or other pathologists nearly three-quarters of the time (30/41, 73.2%). In brief, the study design was prospective in one study [59], retrospective in 22 [3,32,33,36,[38][39][40]42,[44][45][46][47][49][50][51]54,60,61,63,66,67,69], secondary analysis of primary clinical trials in six [37,41,48,53,57,58], and not-explained in 12 [19][20][21]34,35,43,52,55,56,62,65,68]. The number of patients per study ranged from 20 to 688, with median ages of 46-70 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In normal lymphoid cells, genetic insults or oxidative stress inhibits BCL2 to promote apoptosis by increasing the expression of proteins of the BH3 family. In malignant lymphoma cells, overexpression of BCL2 caused by chromosomal translocations and increased gene copy number suppresses the apoptosis and promotes the malignant proliferation of lymphoma cells and finally accelerates the MYC-induced lymphomagenesis [23, 24]. About 30% of DLBCL harbor both BCL2 and MYC overexpression, which is defined as double-expressor DLBCL (DE-DLBCL) [25].…”
Section: Myc Overexpression In Dlbclmentioning
confidence: 99%
“…In the current study, the positive immunohistochemical staining of MYC protein was found to be a valuable predicting factor of DLBCL unfavorable prognosis through univariate and multivariate model analysis, which is consistent with previous studies (Kluk et al., 2012; Yan et al., 2014). Although a molecular study of DLBCL of the OMR was absent, studies of DLBCL in non‐specific position have demonstrated that BCL2 and MYC gene rearrangement, and double/triple‐hit lymphoma, predict a worse overall survival (Horn et al., 2013; Ting et al., 2019). In our study, BCL2 and MYC gene rearrangement, and double/triple‐hit DLBCL, correlated with a significantly lower overall survival rate in the univariate analysis, but no significance was found in the multivariate model.…”
Section: Discussionmentioning
confidence: 99%